Peran Desentralisasi Fiskal Bagi Pembangunan - A, Azulaidin (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
One of the important elements of regional autonomy policy is fiscal decentralization. The importance of this policy is certainly not only to increase the amount of budget that can be managed by the regional government, but it is also expected to be managed to improve regional development. In other words, through this budget, it is hoped that development problems in the region can be resolved. In the context of Medan City, the implementation of fiscal decentralization is expected to overcome the problem of unemployment. Through this policy, it is hoped that the Medan City Government can support the growth of the expected key sectors. can have an impact on the growth of other sectors, increasing output, employment opportunities, and regional income. This can be done, among others, by allocating part of the budget to these key sectors. However, some of the factors above may not necessarily have a positive impact on regional economic development. One of the factors that can be the main obstacle is institutional problems that can be counter-productive to efforts to develop the regional economy, including in overcoming the problem of unemployment. To investigate further, the factual conditions of the policy, the following things need to be questioned: (1) How is the economic structure of Medan City reviewed from the sectoral output structure, demand and supply structure, consumption structure, investment structure and stock changes, export and import structure and gross value added structure (regional income).